LOCAL WISDOM VS MODERN: PERCEPTION ANALYSIS STUDY ON THE RARA ISTIANI WULANDARI DEPICTION IN THE MANDALIKA CIRCUIT MOTOGP EVENT 2022 - Sihombing, Lambok Hermanto; Saputra, Adithiya Wiradinatha (Jurnal Ilmiah Mandala Education (JIME), 2022)
This article discusses the perception of Rara Istiani Wulandari as a rain handler at the MotoGP event held at the Mandalika circuit. Rain handler is a term for someone who is believed to be able to control the rain. Rara Istiani Wulandari is a very phenomenal figure because of her action that attracts attention when controlling rainy weather in the middle of the Mandalika circuit field. In this study, researchers will examine people's perceptions of the rain handler carried out by Rara Istiani Wulandari. Researchers used data sources from Instagram and YouTube. These two platforms were chosen considering that the majority of the community is very close and intensively uses these platforms as part of finding and providing information to the public. The process of selecting data sources is based on a random sampling technique. Researchers will see the level of interaction on each news content, such as the number of significant likes, comments, and viewers. In its implementation, the researcher will use the perception theory proposed by Verderber (1978). This perception theory aims to see how people view the current era of the existence of the rain handler described by the figure of Rara Istiani Wulandari. Furthermore, the researcher also uses the media ecology theory proposed by Marshall McLuhan as a supporting theory, which aims to see the relationship between the media and the perception of Rara Istiani Wulandari as a rain handler. The findings obtained from the research are that people today tend to generalize something practically and realistically by looking at various sides before being poured into an opinion